EVALUASI PENERAPAN PEMERIKSAAN KESEHATAN TENAGA KERJA DI BALAI BESAR PENGEMBANGAN KESELAMATAN DAN KESEHATAN KERJA KOTA MAKASSAR - Ridwan Ridwan; Najmi Kamariah (Jurnal Administrasi Negara, 2019)
Abstract Health inspection activities on the workforce is still a challenge in its application because no initial health checks and special health checks on the workforce. Based on these considerations, this study aims to evaluate the application of labor inspection in the Center for Occupational Safety and Health Development, in accordance with Minister of Manpower and Transmigration No. 02 of 1980 concerning health checks and work safety management. The research method used was qualitative discussion material that discussed health issues at the Center for Occupational Safety and Health Development. Data sources analyzed were the results of interviews, direct observations in the field of services, the general field of labor and document review at the Makassar Center for Occupational Safety and Health Development. Research results related to the implementation of medical examinations in companies are still ineffective because they apply initial and special health examinations, the discussion offered by researchers for BBPK3 to revise or amend, Law No. 1 of 1970 concerning work safety and the application of ISO 15189 on clinical laboratory accreditation so that companies can examine initial, periodic and special occupational health, examine the workforce health of workers to improve efficiency and improve workforce performance higher. Keywords : Health Check, Occupational Health and Safety